1972
DOI: 10.1037/h0032332
|View full text |Cite
|
Sign up to set email alerts
|

The Holtzman Inkblot Technique.

Abstract: After a brief description of the rationale, construction, and structure of the Holtzman Inkblot Technique, this study critically reviews 10 years (1959-1969) of research with this instrument. An impressive body of positive findings is in evidence, but many more studies are needed in most areas covered by this review. The various technical refinements and extensions of this instrument that have been produced should facilitate the appearance of much needed future research. The dearth of relevant studies renders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 62 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…The Holtzman test, however, has met some of the criticisms. In a review, Gamble (1972) concluded: With reference to the formal aspects of the Holtzman Techniquethe basic structure of the instrument, the elaborate reference group norms providedwe can also agree with Forer's (1965) review in finding "the Holtzman Inkblot Technique a very attractive research instrument".…”
supporting
confidence: 53%
“…The Holtzman test, however, has met some of the criticisms. In a review, Gamble (1972) concluded: With reference to the formal aspects of the Holtzman Techniquethe basic structure of the instrument, the elaborate reference group norms providedwe can also agree with Forer's (1965) review in finding "the Holtzman Inkblot Technique a very attractive research instrument".…”
supporting
confidence: 53%
“…The HIT was commended on its excellent reliability for a performance-based technique ( Holtzman et al, 1961 ; Gamble, 1972 ; Holtzman, 1975 ; Anastasi, 1982 ; Lilienfeld et al, 2000 ; Holtzman and Swartz, 2003 ; Darolia, 2016 ), its ability to differentiate individuals with psychopathology from healthy controls and among different psychopathologies ( Holtzman et al, 1961 ; Moseley, 1963 ; Megargee and Velez-Diaz, 1971 ; Leichsenring, 1990 , 1991 ; Darolia, 2016 ), its sensitivity to detect the developmental changes across the lifespan ( Thorpe and Swartz, 1965 , 1966 ; Swartz et al, 1967 ; Darolia, 2016 ), its maintaining a constant number of total responses to the protocols ( Lilienfeld et al, 2000 ), and for the possibility of group administration ( Darolia, 2016 ; Holtzman, 1988 ; Panek et al, 1983 ). All these features represent advantages over the Rorschach in research and clinical assessment, especially when it comes to a situation, where many subjects have to be tested (e.g., academic, job, and military selection).…”
Section: Introductionmentioning
confidence: 99%
“…inter and intra-scorer reliability), leads Gamble (1972) to suggest that it might eventually replace the Rorschach technique as its natural successor.…”
Section: Stimulus Materialsmentioning
confidence: 99%
“…The HIT consists of two tests containing 45 inkblots. It is important, for the purposes of present study, that in the selection of a given blot an important consideration was the ability to "elicit small detail, space, color, and shading determined responses from the subject" (Gamble, 1972). This characteristic of the HIT suggests that generated images are The criteria for inclusion of a given blot into the original HIT set were;…”
Section: Stimulus Materialsmentioning
confidence: 99%
See 1 more Smart Citation